Color Rendering Correctness Estimation of Aerial and Satellite Images and Restoration of Color Balance - I. Anikeeva; A. Chibunichev (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Despite the fact that with a certain degree of generalization our idea of object’s color around us can be considered the same, the problem of estimation of the color rendering correctness is very relevant for image’s radiometric correction. The color rendering correctness is one of the most important indicators of aerial and space images visual (photographic) quality, since it determines the quality of objects brightness features transmission by the image. In aerial and space imaging for phototopographic surveying (Bianco et al, 2015), to date, neither an indicator of color imbalance nor a method for its estimation has been developed, therefore it is not possible to assess objectively the presence and degree of color imbalance. Amethod for quantitative estimating the color imbalance of an image suggested in paper. The criterion for evaluating the image’s color imbalance, a method for it’s determining and experimental verification of the developed method by correcting the image’s color balance are shown.